2021
DOI: 10.3389/fnagi.2021.706569
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Exoskeletal Robot for Locomotor Rehabilitation in Stroke Patients: A Multi-center, Non-inferiority, Randomized Controlled Trial

Abstract: Objective: To investigate the efficacy and safety of a novel lower-limb exoskeletal robot, BEAR-H1 (Shenzhen Milebot Robot Technology), in the locomotor function of subacute stroke patients.Methods: The present study was approved by the ethical committee of the First Affiliated Hospital of Nanjing Medical University (No. 2019-MD-43), and registration was recorded on the Chinese Clinical Trial Registry with a unique identifier: ChiCTR2100044475. A total of 130 patients within 6 months of stroke were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Voluntary ankle dorsi exion movement improved despite the chronic phase. Previous studies in patients with acute and sub-acute stroke have reported improvement in FMA-LE with robot-assisted gait training [31][32][33][34][35][36]. Although some studies have shown similar improvements in FMA-LE after robotassisted gait training in patients with chronic stroke [37,38], the number of sessions or duration of intervention were longer than in our intervention.…”
Section: Discussionmentioning
confidence: 66%
“…Voluntary ankle dorsi exion movement improved despite the chronic phase. Previous studies in patients with acute and sub-acute stroke have reported improvement in FMA-LE with robot-assisted gait training [31][32][33][34][35][36]. Although some studies have shown similar improvements in FMA-LE after robotassisted gait training in patients with chronic stroke [37,38], the number of sessions or duration of intervention were longer than in our intervention.…”
Section: Discussionmentioning
confidence: 66%
“…In adults, stroke is the major factor causing a long-time impairment. The occurrence of hemiplegia is growing annually as a result of an aging population and in emergency treatment, resulting in considerable medical and societal consequences [ 4 ]. Motor loss is a very well consequence of stroke because it impairs muscle function and movement.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement in gait-related activities includes not just walking activity but also taking into account the context and surroundings as it changes when walking, such as uneven terrain, level differences, avoiding obstacles, and crowding [ 5 , 6 ]. Most stroke patients have an asymmetric walking pattern, lower-extremity stiffness on the affected (hemiplegic) side, and impaired single stance and weight transfer capacity, restricting their locomotor function [ 4 ]. While the majority of recovery is expected to occur within the first few weeks following hemiplegia, individuals may continue to make progress on functional activities for many months [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations